Pilot testing models of task shifting for the care of severe mental illness in South Africa - Sibeko, Ntokozo Goodman (Department of Psychiatry and Mental Health, 2018)
Background Mental and substance use disorders cause significant disability worldwide. In spite of the availability of evidence-based treatment, non-adherence rates remain high in people with severe mental illness. Mental health services are however under-resourced, especially in low- and middle-income countries. Interventions that employ task shifting, the delegation of health care delivery tasks to less specialized health workers, have the potential to address this resource shortage. Community health workers, while an established and important delivery agent for task shifting in many forms of chronic illness, including mental illness, have lacked access to standardized structured training in mental health. Together with novel approaches such as mobile health, task-shifting interventions have the potential to improve adherence and clinical outcomes for MHSU, thus reducing the burden on stretched mental health resources. While the evidence for the effectiveness of task shifting interventions is growing, it is unclear whether the combination of a task shifting intervention with mobile health would be acceptable and feasible in low resource settings. It is also unclear to what extent a structured mental health training programme would result in improved knowledge, confidence and attitudes amongst community health workers. Methods First, I conducted an appraisal of current evidence for interventions delivered by non-specialist workers for mental illness in Sub-Saharan Africa. The aim was to characterize the types of such interventions that have been carried out in Sub-Saharan Africa, to ascertain extent of use of non-specialist workers; the outcomes explored; any acceptability and feasibility findings; as well as any efficacy outcomes. Second, I developed and piloted two task shifting interventions geared at improving care for severe mental illness in Cape Town, and evaluated their acceptability, feasibility and preliminary effectiveness. Systematic review: For the systematic review, eligible studies published prior to 21 June 2017 were identified by searching the Cochrane library, PsychInfo, and Medline databases; as well as the World Health Organization International Clinical Trials and Pan African Clinical Trials Registries. The bibliographies of study reports for all eligible trials were scanned for additional studies. Included trials were those of interventions a) delivered by non-specialist health workers for b) adult populations (18-65 years) with c) psychiatric disorders diagnosed in line with ICD or DSM classification systems in d) Sub-Saharan Africa. No restriction was placed on the nature of the psychiatric disorder. Pilot randomized controlled trial: A pilot randomized controlled trial was conducted, in which 77 participants with severe mental illness were recruited from Valkenberg psychiatric hospital in Cape Town, with 42 randomized to receive the intervention and 37 to receive treatment as usual. In the intervention arm, a treatment-partner selected by the participating MHSU underwent a psychoeducation and treatment-partner contracting session. The intervention pair then received two text message reminders of clinic visit appointments monthly. The primary outcomes were acceptability and feasibility of the intervention, measured through qualitative interview and process evaluation at 3 months post-discharge. Secondary outcomes for efficacy were 1) adherence to the first clinic visit; 2) any readmission in the 9 months following discharge; 3) quality of life; 4) symptomatic relief; and 5) medication adherence. These efficacy measures were conducted at baseline and again at 3-month study review. Between-group comparisons were done using an intention to-treat ANOVA analysis for efficacy outcomes. Community Health Worker Training Intervention: My second task shifting intervention was a quasi-experiment evaluating whether structured mental health training would improve the knowledge and skill of community health workers while improving their confidence and attitudes towards mental illness. A training programme was developed in partnership with the Western Cape Department of Health, and piloted with 58 community health workers who had not previously received mental health training. Mental health knowledge and skill were measured though the use of case vignettes and the Mental Health Knowledge Schedule (MAKS). Confidence was measured using the Mental Health Nursing Clinical Confidence Scale (MHNCCS), while attitudes were measured using the Community Attitudes towards the Mental Ill Scale (CAMI). Measures were conducted at baseline, at the end of the training, and again 3 months after the end of training for the knowledge and skill measures. Daily evaluation questionnaires were used to establish acceptability, and a training evaluation questionnaire was used to obtain further acceptability data, as well as to establish feasibility of the training intervention. T-tests and regression models were used to test changes in questionnaire scores before and after each intervention, adjusting for baseline scores. Quantitative data were entered and analysed using STATA 10.0 for the pilot randomized controlled trial and the R statistical programme for the CHW intervention, while qualitative data were managed and analysed using NVIVO 8, a qualitative analysis programme for all analyses, for which a grounded theory approach was used, followed by thematic analysis. Ethics and registration: Ethical approval was obtained from the University of Cape Town Human Research Ethics Committee, Faculty of Health Sciences for the treatment partner and mobile health intervention (HREC REF: 511/2011) and for the community health worker training intervention (HREC 913/2015). Both interventions were registered on the Pan African Clinical Trials Registry (PACTR201610001830190 and PACTR201610001834198 respectively). Finally, Health Impact Assessment Unit clearance was obtained from the Western Cape Department of Health for both trials (RP168/2011 and WC_2016RP59_635 respectively). The systematic review was registered on the International prospective register of systematic reviews (PROPSERO) (CRD42017065190)). Results Systematic Review: Due to heterogeneous methods and treatment outcomes, a meta-analysis was not possible. A narrative synthesis is thus presented. Fifteen trials of interventions delivered by non-specialist workers (5087 participants) were identified. In each of the trials, the intervention was acceptable and feasible, with preliminary efficacy findings favouring the interventions. Pilot randomized controlled trial: The treatment partner and text message intervention components were acceptable. While the treatment partner and psychoeducation components were feasible, the text message component was not, as a consequence of several socioeconomic and individual factors. While efficacy outcomes favoured the intervention, they did not reach statistical significance due to the small sample size. Community Health Worker Training Intervention: Mental health knowledge improved as demonstrated by improved diagnostic accuracy on case vignette response. Sixty-three percent of participants demonstrated improved accuracy in making a diagnosis, with a roughly two-fold increase in performance in these individuals. There was a significant increase in the average scores on the Mental HeAlth Knowledge Schedule pre- to post training (t = -4.523, df = 55, p < 0.001, N=56). This improvement was sustained at 3 months after the end of training assessment scores (t = -5.0, df = 53, p < 0.001, N = 54). There was a significant increase in the average Confidence scores pre-intervention (mean SD): 45.25 (9.97) to post-intervention 61.75 (7.42), t-test: t = -8.749, df = 54, p < 0.001, N=58). Attitude scores (n=45) indicated no change in authoritarian attitudes [mean (SD): Pre 27.87 (2.97); Post 26.38 (4.1), t = 2.720, p-value = 0.995], while benevolence [mean (SD): Pre 37.67 (4.46); Post 38.82 (3.79), t = -1.818, p-value = 0.038] and social restrictiveness [mean (SD): Pre 24.73 (4.28); Post 22.4 (5.3), t = -2.960, p-value = 0.002] attitudes showed improvement pre- and post-training, as did tolerance to rehabilitation of the mentally ill in the community (t = 2.176, p-value = 0.018). Participants responded well to training, appraising it as acceptable and appropriate to their work. They expressed a need for a longer training programme with further training on substance use and geriatric disorders. Stakeholder participation was consistent and contributed to the feasibility of the intervention. Conclusions A review of task shifting interventions by non-specialist health workers indicates that these have yielded positive outcomes for mental health service users in published trials. Such interventions have the potential for reducing the mental health treatment gap in low and middle income countries in a cost-efficient way. Further work is however required to develop specific treatment approaches for particular disorders, and to assess the outcomes of such interventions, including cost-efficiency measures. The measures of outcome used in this field remains somewhat disparate; the development of a common research agenda may assist in developing and replicating further investigations and generalising findings. A treatment-partner intervention is acceptable and feasible in a low- and middle-income setting such as ours. Careful work is, however, needed to ensure that any additional components of such an intervention, such as mobile health, are tailored to the local context. Appropriately powered studies are needed to assess efficacy. Structured training in mental health is acceptable and feasible in our setting. The training intervention led to an improvement in knowledge and skill amongst community health workers while improving confidence and attitudes. Participation of policy stakeholders was key in ensuring the success of the intervention. There is a need for interventions evaluating the outcomes of community health worker training to provide more detailed descriptions of their training interventions. More focus must be placed on measuring service and end-user outcomes to improve the rigor and quality of such investigations, with well-powered randomized controlled trials being best placed to answer questions regarding efficacy and cost-effectiveness. In summary, my systematic review, and my pilot task-shifting interventions in the South African context indicate that task shifting interventions such as these are acceptable and feasible, offering a promising solution to addressing the under-resourcing of mental health care. However, interventions should ideally be tailored to the specific communities they target, taking into account specific individual, community, technological, and sociodemographic factors. Future training interventions should provide more detailed descriptions of programme components and focus on measuring patient outcomes, while all task shifting interventions may benefit from incorporating an evaluation of cost effectiveness. Task shifting presents a viable and accessible opportunity for creative innovation and as we work towards achieving mental health for all.